Effect of micropattern on behaviour of fibroblasts - Wong, Ziling (2016)
With extension of life expectancy, skin aging has becomes a popular research topic due to healthcare and aesthetic reasons. Aging is more visibly evident in skin than in other organs as skin displayed physical signs of aging such as wrinkles and sagging of skin. Several anti-aging strategies have been developed during the past years but the attempts to understand the interaction between cell and extra-cellular matrix (ECM) in the process of skin aging remains relatively unexplored. In this project, we studied the fate of human dermal fibroblast, neonatal (nHDF) grown on fibronectin micropatterns in attempt to understand the cell-matrix interaction and its effect on skin aging. The nHDFs will be cultured on the coverslips with and without fibronectin micropattern. These were followed by UV irradiation to induce senescence in nHDFs. Characterisation of the cells will be carried out using senescence markers as well as other biological reagents. Under the UV irradiation induction, the proliferation rate was slowed down significantly in nHDFs grown without micropattern than with pattern. Also, the % of senescence cells was higher in nHDFs grown without micropattern than with pattern. With further characterisation, cell senescence was found to be mediated by arrangement of actin filaments. This study showed that micropatterns have a significant effect on nHDFs’ senescence induced by UV irradiation. The matrix mediated senescence is dependent on the filament alignment. Future studies are recommended to identify the key factors involved in the regulation of cell senescence induced by UV irradiation.